(untitled) (Modern education and development, 2024)
This article delves into the assessment system of the writing process, highlighting its role in improving writing skills, offering a framework for effective evaluation, and exploring the key methodologies used to assess various stages of writing. It examines both traditional and modern approaches to writing assessment, focusing on their impact on learners’ performance. This study also includes a detailed analysis of the challenges and opportunities inherent in assessing the writing process. The aim is to provide educators with a comprehensive understanding of how assessment methods can enhance the teaching and learning of writing.